Association between Mediterranean diet adherence and colorectal cancer: a dose-response meta-analysis. Issue 6 (2nd May 2020) - Zhong, Yuan; Zhu, Yan; Li, Quanpeng; Wang, Fei; Ge, Xianxiu; Zhou, Guangxin; Miao, Lin
Abstract: Background: Mounting epidemiologic studies have investigated the potential inverse association between Mediterranean diet (MD) adherence and colorectal cancer (CRC) incidence and mortality. Objectives: This meta‐analysis aimed to investigate the association between MD adherence and CRC incidence and mortality. Methods: PubMed, Embase, and Web of Science were searched to identify eligible studies through September 2019. A random-effects model was used to estimate summary RRs and 95% CIs. Results: This meta-analysis included 13 prospective cohort studies, of which 9 reported CRC incidence and 5 reported CRC mortality. The summary RR of CRC incidence was 0.90 (95% CI: 0.84, 0.96) for highest compared with lowest MD adherence and 0.96 (95% CI: 0.94, 0.99) per 2-score increase in MD adherence. The summary RRs for highest compared with lowest MD adherence were 0.82 for rectal cancer (95% CI: 0.71, 0.95), 0.94 for proximal colon cancer (95% CI: 0.87, 1.02), and 0.91 for distal colon cancer (95% CI: 0.79, 1.04). Neither the summary HR of overall mortality for highest compared with lowest pre- and postdiagnosis MD adherence, nor the summary HR of CRC-specific mortality for highest compared with lowest prediagnosis MD adherence achieved a value with statistical significance. Conclusions: Our meta-analysis supports the inverse association of MD adherence with CRC incidence, but not with overall mortality or CRC-specific mortality among those diagnosed with CRC.